Traversing the Origin and Diaspora: Leila Aboulela's Minaret in the Light of Miriam Cooke's Transnational Muslim Feminist Sensibility. Issue 4 (1st October 2020) - Ishaque, Nausheen; Bibi, Sadia; Afzal Faheem, Muhammad; Hussnain Rasheed, Chaudhry
Abstract: This paper explores Leila Aboulela's Minaret 1 in terms of its protagonist's journey between the Muslim origin and global diaspora. For its theoretical underpinning, the paper draws on transnational Muslim feminist paradigm with Miriam Cooke as its chief proponent. With this, the paper probes how the convergence of the religious origin and contemporary diaspora creates a globally accepted, new identity for Muslim women across the globe. Muslim migrant women from the third world, who are already faced with double colonization, are now struggling against Islamophobia as yet another oppressive force. Aboulela's protagonist, Najwa, experiences similar difficulties, especially when it comes to identity construction and meaning-making in her life abroad. She, being a Muslim woman, revisits her religion in search of self-actualization and awareness about the global ummah without any geographical boundaries. This study is, therefore, an attempt to see the variegated identity of Aboulela's protagonist as a Muslim woman and a global citizen.